2001
DOI: 10.1071/mf00047
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and distribution of the bigeye flounder Hippoglossina macrops off Northern Chile

Abstract: Bathymetric distribution and stomach contents of the bigeye flounder captured during November 1995 were analysed. Bathymetric distributional pattern differed among age classes, with younger fish inhabiting shallower waters while older fish occupied all depths sampled. For each sex, the densities were greatest at shallower depths and decreased constantly with depth. Differences in feeding habits with fishing ground, depth and age classes were found. Feeding is characterized by consumption of juvenile squat lobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This link seems to be the ability of P. monodon to tolerate severely hypoxic to anoxic conditions for several days and to migrate between the two habitats, possibly on a daily basis. Anoxic or severely hypoxic conditions at the seafloor may actually benefit P. monodon, as they provide shelter from predatory demersal fish such as the bigeye flounder (Hippoglossa macrops), which is an important predator of P. monodon on the better-oxygenated shelf off Chile (Villarroel et al 2001). The observed p crit of 0.5 kPa is one of the lowest recorded for metazoans that migrate into or are endemic within OMZs, most of which have a p crit > 1.0 kPa (Seibel 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This link seems to be the ability of P. monodon to tolerate severely hypoxic to anoxic conditions for several days and to migrate between the two habitats, possibly on a daily basis. Anoxic or severely hypoxic conditions at the seafloor may actually benefit P. monodon, as they provide shelter from predatory demersal fish such as the bigeye flounder (Hippoglossa macrops), which is an important predator of P. monodon on the better-oxygenated shelf off Chile (Villarroel et al 2001). The observed p crit of 0.5 kPa is one of the lowest recorded for metazoans that migrate into or are endemic within OMZs, most of which have a p crit > 1.0 kPa (Seibel 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Even though oxygen concentration may have phenotypic and/or deleterious effects on organisms in general (Crispo and Chapman 2008; Ulloa and Pantoja 2009), it has been shown that P. monodon has physiological adaptations to live in low oxygen zones. The shallow OMZ may even represent a predation refuge for the species (Villarroel et al 2001). It is unknown the extent of the OMZ and its effect on benthic communities (Thiel et al 2007) so maybe, indirectly, it is still affecting P. monodon in spite of its own adaptability to low oxygen regimes.…”
Section: Discussionmentioning
confidence: 99%
“…We considered S. capensis to be a fish with low vagility. Finally, H. macrops , like other flatfishes, performs only small migratory movements from shallow to deep waters, associated with ontogenetic changes in diet (Villarroel et al. , 2000).…”
Section: Methodsmentioning
confidence: 99%